1999
DOI: 10.1144/0050153
|View full text |Cite
|
Sign up to set email alerts
|

Middle Oxfardian to Volgian sequence stratigraphy of the Greater Shearwater area

Abstract: A Middle Oxfordian to Volgian sequence stratigraphic model for the Greater Shearwater area is presented. This model builds on the genetic stratigraphic sequences of Partington et al. (19936), refining the position of key stratigraphic surfaces with an additional emphasis on sequence boundary description. Most stratigraphic surfaces are believed to be related to tectonic events superimposed on a gradual rise in relative sea-level from the Middle Oxfordian to Volgian. Biostratigraphic information drawn from thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 15 publications
(10 reference statements)
0
9
0
Order By: Relevance
“…Zechstein salt halokinesis and post-Jurassic fault movements render attempts to determine exact amounts of Late Jurassic uplift extremely complex and inaccurate in this area, with previous studies implying the ridge was submerged throughout the Jurassic rift phase (Zeigler, 1990;Rattey and Hayward, 1993;Erratt et al, 1999;Jeremiah and Nicholson, 1999;Fraser et al, 2003;Sansom, 2010).…”
Section: Accepted Manuscriptmentioning
confidence: 96%
See 1 more Smart Citation
“…Zechstein salt halokinesis and post-Jurassic fault movements render attempts to determine exact amounts of Late Jurassic uplift extremely complex and inaccurate in this area, with previous studies implying the ridge was submerged throughout the Jurassic rift phase (Zeigler, 1990;Rattey and Hayward, 1993;Erratt et al, 1999;Jeremiah and Nicholson, 1999;Fraser et al, 2003;Sansom, 2010).…”
Section: Accepted Manuscriptmentioning
confidence: 96%
“…Previous models have indicated that the Josephine Ridge area was submerged during the Oxfordian and Kimmeridgian (Zeigler, 1990;Rattey and Hayward, 1993;Jeremiah and Nicholson, 1999;Fraser et al, 2003), with modelling of Upper Oxfordian submarine fan systems prograding from the Fulmar shelf and interpreted to cross-cut the Josephine Ridge (Jeremiah and Nicholson, 1999;Fraser et al, 2003). If, as we propose, the Judy Horst was subaerially exposed, forming a topographic high, then it appears unlikely that sediment would have been able to cross either arm of the Central Graben, to be deposited on the opposing side Although subaerial exposure of the Judy Horst may identify it as a source of reservoir quality sediment, the estimated size of the Judy Island at c.350 km 2 would have been insufficient to source large scale sedimentary systems with reservoir potential.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Howell et al (1996) offered a convincing account of the relationship between Fulmar Formation depocentres and the hinterland, with shoreface fairways forming at entry points in the relays in the graben system. This model offered a compelling fit with the recognition that the Oxfordian fairways were in turn located at the northern and southern limits of a series of en-echelon graben developing during the Oxfordian, with gradual retreat of these fairways away from the basin centres and ultimately onto the platforms in the Kimmeridgian (Erratt et al 1999;Jeremiah & Nicholson 1999). Heavy mineral analysis of the Fulmar sands indicates a progressive un-roofing of the hinterland, with sediments derived from finergrained and mixed lithologies in Triassic and Middle Jurassic sequences, indicating a less effective reservoir provenance than those feeding the South Viking Graben and Moray Firth systems.…”
Section: Comparing the Upper Jurassic Of The Central Troughmentioning
confidence: 96%
“…sequences, forming local sediment traps, thereby reducing the potential for sediment bypass. & Nicholson 1999). These reservoirs are relatively thin compared with their ESB counterparts (Magnus Field well log for comparison).…”
Section: The Role Of Salt Withdrawalmentioning
confidence: 98%
See 1 more Smart Citation